2016
DOI: 10.1002/jsfa.8002
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive prediction of pigment content in lettuce based on visible–NIR spectroscopy

Abstract: The proposed models were adequate for estimating lettuce pigments in a quick and non-destructive way, representing an alternative to conventional measurement methods. Prediction accuracies were improved by using the detrending, smoothing and first derivative pretreatments to the original spectral signatures prior to estimating lettuce chlorophyll, carotenoid and anthocyanin content, respectively. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The concentration (mg/g) of included leaf pigments namely chlorophyll a, chlorophyll b, β-carotene, anthocyanin, and lutein were spectrophotometrically determined using optical densities (OD) of 480 nm, 495 nm, 663 nm, 645 nm, and 700 nm according to the procedure described by Ben Ghnaya, Charles, Hourmant, Ben Hamida, & Branchard (2007) and Gholami, Rahemi, Kholdebarin, & Rastegar (2012) and the adapted pigment equations (1-4). Anthocyanin pigment concentration (mg/g) that is based on cyanidin-3-glucoside extraction was adapted from the procedure done by Lee, Durst, & Wrolstad (2005) and Steidle Neto et al (2016) which is the pH-differential method that dilutes 0.1% of hydrochloric acid (HCL) to every 1 ml of leaf extract. Potassium chloride (KCl) and sodium acetate (C 2 H 3 NaO 2 ) buffers for pH 1.0 and 4.5, respectively, were diluted to leaf extracts before 30 minutes of centrifugation, then, samples undergo spectrophotometric measurement in the 520 nm and 700 nm wavelengths (5).…”
Section: Lettuce Pigment Preparation and Uv-vis Spectrophotometric Assay Of Phytopigments And Nutrient Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentration (mg/g) of included leaf pigments namely chlorophyll a, chlorophyll b, β-carotene, anthocyanin, and lutein were spectrophotometrically determined using optical densities (OD) of 480 nm, 495 nm, 663 nm, 645 nm, and 700 nm according to the procedure described by Ben Ghnaya, Charles, Hourmant, Ben Hamida, & Branchard (2007) and Gholami, Rahemi, Kholdebarin, & Rastegar (2012) and the adapted pigment equations (1-4). Anthocyanin pigment concentration (mg/g) that is based on cyanidin-3-glucoside extraction was adapted from the procedure done by Lee, Durst, & Wrolstad (2005) and Steidle Neto et al (2016) which is the pH-differential method that dilutes 0.1% of hydrochloric acid (HCL) to every 1 ml of leaf extract. Potassium chloride (KCl) and sodium acetate (C 2 H 3 NaO 2 ) buffers for pH 1.0 and 4.5, respectively, were diluted to leaf extracts before 30 minutes of centrifugation, then, samples undergo spectrophotometric measurement in the 520 nm and 700 nm wavelengths (5).…”
Section: Lettuce Pigment Preparation and Uv-vis Spectrophotometric Assay Of Phytopigments And Nutrient Concentrationmentioning
confidence: 99%
“…The most related techniques in this study are partial least square regression and quadratic regression using RGB and HSI color spaces (Table 5). The developed DT-MSRGP model completely bested these techniques by Steidle Neto et al (2016) and Yang et al (2016) in predicting chlorophylls, beta-carotene, anthocyanin, lutein, and vitamin C concentrations. Though Steidle Neto et al (2016) has a 9% advantage in the prediction accuracy of anthocyanin, their laboratory technique used 99.5% acetone instead of 75%, and the concentration convention used is mg/kg instead of mg/g.…”
Section: Phytopigments and Nutrient Concentration Using Feature-based Machine Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, the other carotenoids considered in our study have never been predicted in milk samples using MIR-ATR and fluorescence spectroscopy. However, different studies showed that it is possible to predict concentrations of β-cryptoxanthin, lutein, zeaxanthin [36,37], the sum of carotenes [38] and the sum of carotenoids [37,39,40] in vegetables using NIR spectroscopy. The equations used to predict the concentrations of these different carotenoids in vegetable samples are more precise than those applied in the current study.…”
Section: Prediction Of Carotenoids and Vitaminsmentioning
confidence: 99%